Parent-Child Interactions and the Development of Critical Thinking in Early Childhood: A Systematic Literature Review - Indah Andika Octavia; Widia Sri Ardias; Rahman Pranovri Putra; Mai Tiza Husna; Maysyarah (Psympathic : Jurnal Ilmiah Psikologi, 2026)
In this systematic literature review, the role of parent-child interactions in supporting critical thinking development during early childhood was examined. The adoption of PRISMA framework in the review led to the identification of 500 articles from national and international scientific databases out of which 25 empirical studies satisfied the inclusion criteria. The results showed that responsive parent-child interactions including democratic parenting, inquiry-based communication, family literacy activities, and questioning strategies significantly supported the analytical reasoning, problem-solving, and evaluative thinking of children. A distinctive observation was that digitally mediated questioning strategies such as interactive storytelling tools enhanced deeper parent-child discussions and stimulated reflective reasoning. However, the methodological limitations identified include the dominance of cross-sectional designs, small or culturally specific samples, and inconsistent definitions of critical thinking in early childhood studies. The evidence suggested that structured parental participation meaningfully supported higher-order cognitive development despite the limitations. This review offers implications for parent education programs and emphasizes the need for robust longitudinal and cross-cultural studies.